DO STUDENTS’ SELF-ASSESSMENT AND ENGLISH WRITING SKILL CORRELATE EACH OTHER? - siti zahroh (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
The aim of this study was to investigate whether students with good self-assess ability have a strong relationship with their English writing skill particularly in writing analytical exposition text. The correlational research design was used in this study in order to measure the correlational between students’ self-assessment and their English writing skill. The data were collected from thirty one (31) sophomore students from F-Class of SMAN 3 Malang which was selected by clustering sampling. They were asked to self-assess their task after writing analytical exposition text which was their current material in English class by giving them a checklist questionnaire regarding the text they had written. The questionnaire consist of twenty-five questions with four big parts; format, content and organization, mechanics and spelling, and language used. To analyze the data Pearson-Product Moment from SPSS v.16 was used. The result of the calculation data was found that the p value (2-tailed) was 0.000 (p < 0.01) indicating that students self-assess did have a strong relationship with their English writing ability which was automatically indicated that students who were aware with their self-assessing ability would also have a better ability in English writing ability. Regarding all those findings, self-assessment is highly recommended for both teacher and students particularly to be applied in classroom activity as a learning method in order to track students’ sense of self-analysing or self-assessing on their English writing skill. Keyword: self-assessment, writing ability, analytical exposition.